2020
DOI: 10.1007/s00425-020-03449-4
|View full text |Cite
|
Sign up to set email alerts
|

Shoot tip necrosis of in vitro plant cultures: a reappraisal of possible causes and solutions

Abstract: Main conclusion Shoot tip necrosis is a physiological condition that negatively impacts the growth and development of in vitro plant shoot cultures across a wide range of species. Abstract Shoot tip necrosis is a physiological condition and disorder that can arise in plantlets or shoots in vitro that results in death of the shoot tip. This condition, which can spread basipetally and affect the emergence of axillary shoots from buds lower down the stem, is due to the cessation of apical dominance. STN can occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 179 publications
(324 reference statements)
0
20
0
3
Order By: Relevance
“…Due to the high heterogeneity of ingredients that make part of culture media formulations and other additional factors, such as plant genotype or growth conditions, the study of nutritional requirements applied to unknown medicinal plants leads to the design of complex multivariate experimental designs (Nezami-Alanagh et al, 2017;Teixeira da Silva et al, 2020). In the last decade (Hesami and Jones, 2020;Niazian and Niedbala, 2020), several ML algorithms have been successfully employed as alternative to traditional statistical methods and/or response surface methodology (RSM) to identify factors and interactions on complex, non-linear and non-deterministic process such as PTC (Landin et al, 2009;Gago et al, 2010a,c;Nezami-Alanagh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high heterogeneity of ingredients that make part of culture media formulations and other additional factors, such as plant genotype or growth conditions, the study of nutritional requirements applied to unknown medicinal plants leads to the design of complex multivariate experimental designs (Nezami-Alanagh et al, 2017;Teixeira da Silva et al, 2020). In the last decade (Hesami and Jones, 2020;Niazian and Niedbala, 2020), several ML algorithms have been successfully employed as alternative to traditional statistical methods and/or response surface methodology (RSM) to identify factors and interactions on complex, non-linear and non-deterministic process such as PTC (Landin et al, 2009;Gago et al, 2010a,c;Nezami-Alanagh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…STN is a physiological condition that can emerge in in vitro plantlets or shoots and affect propagation by causing tissue death (Bairu et al 2009). STN has been reported in several arboreal and shrubby plants (Teixeira da Silva et al 2020). Furthermore, the usage of short shoots (less than 0.5 cm in length) affects the elongation phase and delays roots appearance, which can lead to nutrient deficiency in the plant (Martínez et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in vitro cultures may be adversely affected by NaOHinduced nutritional disorders since it has been demonstrated that the concentrations and ratio of certain nutrients can affect the sensitivity of cells to growth regulators and other component of the medium as well as morphogenesis and differentiation (Leifert et al, 1995;Oberschelp and Goncalves, 2018). Nutrient deficiency or imbalance can cause abnormal physiological responses in plant cultures such as hyperhydricity, callus formation and necrosis (Reed et al, 2013;Teixeira da Silva et al, 2020). Additionally, plant cells and tissues performance may also be adversely affected by the alteration of metabolic pathways and osmotic adjustments.…”
Section: Salt Stressmentioning
confidence: 99%